The Right to Migrate: A Human Rights Response to Immigration Restrictionism in Argentina - David C. Baluarte (Washington University Global Studies Law Review, 2019)
Within days of President Donald Trump’s 2017 Executive Orders on border security and immigration enforcement, President Mauricio Macri of Argentina issued a Decree to address what he declared was an urgent problem of immigrant criminality. The timing of the two Presidents’ actions triggered concerns that U.S.-style restrictionist immigration regulation was spreading to South America, a continent that has taken progressive steps towards recognizing the human rights of migrants in recent years. Until Macri’s 2017 Decree, Argentina was considered a leader in this regard, with its 2004 immigration law that boldly codified a “right to migrate” and included robust substantive and procedural protections for immigrants. While the Decree marked the end of an era of progressive immigration policy in Argentina, the persistence of international human rights protections for migrants could provide the means to uphold key aspects of the right to migrate. This Article tracks jurisprudential developments under the 2004 law, and then demonstrates how the 2017 Decree undermined many of the advances achieved under the prior legislative framework. The Article also provides an overview of current litigation to defend the immigrant bill of rights and key procedural and judicial protections. The Article argues that the application of international human rights law on migration could fend off some of the more pernicious features of the 2017 Decree in Argentina. The Article concludes that the right to migrate in Argentina has been weakened, but that its essence will persist if the Argentine judiciary reinforces human rights protections for migrants.
Keywords: donald trump; border security; immigration; immigration law; international law; executive order; latin america; immigration restrictionism; restrictionist; south america; argentina; migration; migrant